2021
DOI: 10.1186/s12909-021-02746-0
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on applying holistic health care model on medical education behavioral intention: a theoretical perspective of planned behavior

Abstract: Background This study aimed to apply the theory of planned behavior to identify the medical education behavioral intention of holistic healthcare on teachers and students who influence the medical and healthcare profession, as a revised future direction for hospitals to continue to implement holistic healthcare. Methods This cross-sectional study was performed from April to May 2020. A questionnaire survey was conducted with the clinical teachers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Literature review revealed that there was a lack of publications focussing on the intentions, and its predicting factors, of health science students' to pursue PGx and PM-related training after graduation. The Theory of Planned Behaviour (TPB) has been continuously applied in a great spectrum of healthcare issues, including the investigation of health science students' intentions for further education [17][18][19][20]. According to TPB, attitudes are considered as a critical factor affecting individuals' intentions for future behaviour.…”
Section: Research Framework Of the Proposed Model On Students' Intent...mentioning
confidence: 99%
“…Literature review revealed that there was a lack of publications focussing on the intentions, and its predicting factors, of health science students' to pursue PGx and PM-related training after graduation. The Theory of Planned Behaviour (TPB) has been continuously applied in a great spectrum of healthcare issues, including the investigation of health science students' intentions for further education [17][18][19][20]. According to TPB, attitudes are considered as a critical factor affecting individuals' intentions for future behaviour.…”
Section: Research Framework Of the Proposed Model On Students' Intent...mentioning
confidence: 99%
“…The values of both groups are greater than 0.5, which is the acceptable value factor loadings [71]. The CR is a measure of the internal consistency of a scale item [72]. The Cronbach's α of the four dimensions all reached a credibility standard of more than 0.5 [73,74], indicating that all of the data the study collected are valid.…”
Section: Path Analysis and Pls-semmentioning
confidence: 99%
“…Our research shows that there is statistical significance in the PCB of air pollution prevention behaviors in both groups, greater than SN (Greater Taipei Metropolitan Group: β = 0.334, t = 5.547 > 3.29; New Taipei City Group β = 0.387, t = 2.967 > 2.58). The PBC for the parents of both groups affects their respective BI [2,56,72,86] associated with air pollution prevention, and that PBC is the main factor influencing their BI.…”
Section: Influence Of Perceived Behavioral Control (Pbc)mentioning
confidence: 99%
“…The composite reliability (CR) is a measure of the internal consistency of a scale item and is much like Cronbach's α [47], which is a measure of the factor variance. If each factor value is greater than 0.7, then the value indicates that the internal consistency or variation of each factor meets the credibility standard [48,49].…”
Section: Path Analysis and Pls-semmentioning
confidence: 99%
“…The results of this study show that there is no statistically significant difference in the PCB of air pollution prevention behaviors in both groups. The PBC for the parents of both groups affect their respective BI [9,36,38,47] associated with air pollution prevention with PBC being the main factor influencing their BI [9,37,38].…”
Section: Influence Of Perceived Behavioral Controls (Pbc)mentioning
confidence: 99%